Effect of clinoptilolite supplementation on the nutritive value of oil palm frond - Wan Abdullah, Wan Mohd. Madhi (2014)
In this paper, the effect of clinoptilolite with and without supplementation on the nutritive value of oil palm fronds (OPF) was studied. Five different levels of clinoptilolite (0-5%) were supplemented on OPF and the effects on the nutritive values were determined; dry matter (DM), total nitrogen (N), crude protein (CP), crude fat (EE), crude fibre (CF), total ash (ASH), calcium (Ca) and phosphorus (P) using the AOAC standard methods. Nitrogen free extract (NFE), total digestible nutrient (TDN) and metabolizable energy (ME) were calculated by differences. Increasing levels of clinoptilolite resulted in some changes in the nutritive values of OPF, except in its EE content.